Women's Rights and Human Rights - Grimshaw, P. author. aut Link
XXI, 318 p.
Keywords: This international collection of historical work explores the breadth and creativity of women's struggles for human rights, citizenship and social justice across the world. It brings together twenty contributions by scholars in women's history, whose work reflects the global reach of the International Federation for Research in Women's History. In addition to presenting studies by well known scholars in the United States and Europe, the book is distinctive in also bringing the work of scholars from regions such as South and East Asia and the Pacific to the attention of an international audience.